Patient and treatment characteristics of emergency presentations due to immune-mediated toxicities. (March 2022) - Nahm, Sharon H.; Heywood, Richard; Callaghan, Sophia; Serra-Bellver, Patricio; Gupta, Avinash; Cooksley, Tim; Lorigan, Paul
Abstract: Background: The prevalence of immune-mediated toxicities from immune checkpoint inhibitors (ICIs) is well described. However, the characteristics and treatment patterns for patients with emergency presentations owing to immune-mediated toxicity are less well known. Materials and methods: This study reviews all emergency presentations in patients treated with ICI at a single centre between May 2018 and March 2020. The aims were to describe and quantify patient and treatment characteristics, toxicity type and outcomes. Results: 1165 patients were treated with ICI, and there were 597 emergency presentations in 370 patients. Of these, 191/597 (32%) were owing to an immune-mediated toxicity, median age was 64 years, and 127/191 (67%) were men. The most common tumour types were melanoma (53%) and lung cancer (22%), and the most common ICI received was ipilimumab + nivolumab combination immunotherapy (42%), followed by pembrolizumab monotherapy (21%) and nivolumab monotherapy (20%). The median number of cycles received was three (range 1–54), and 75/191 (39%) had previous ≥ grade 2 immune-mediated toxicity. 29% patients required second-line immunosuppression. The median time in the hospital was four days. There was a rising number of emergency presentations reflecting overall increasing use of ICI. Conclusions: Over a quarter of patients treated with ICI had an emergency presentation, and immune-mediated toxicity accounted for 32% of these. A diagnosis of melanoma, treatment with combination immunotherapy and previous ≥ grade 2 immune-mediated toxicity were common in patients with immune-mediated toxicity. These data allow better identification of patients likely to require admission and forward planning for acute oncology services. Highlights: Over 25% of patients on immune checkpoint inhibitors had an emergency presentation. 32% of these were owing to an immune-mediated toxicity. Common factors were having melanoma and receiving combination immunotherapy. 39% had previous ≥ grade 2 immune-mediated toxicity. Second-line immunosuppression was required in 29% of patients.